2017
DOI: 10.1111/jfpp.13378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing on stilbenes and biogenic amines in red grape winemaking with stem contact maceration

Abstract: Stem contact maceration is a technique used in red winemaking for wines poor of phenolic constituents (tannins) in order to improve organoleptic characteristics and ensure color stability over time. This article investigates how the presence of different amounts of de‐stemmed bunches affects stilbenoids, known for their nutraceutical properties and biogenic amines (BAs), known for their adverse physiological and toxicological effects, at racking and after 24 months of storage in Primitivo wine. Stilbenes found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, biogenic amines (B.A.s) among bioactive compounds conducted on different grape varieties have been intensively investigated recently due to their effects on the quality, safety, and nutraceutical properties of fruit juices and wines [ 4 ]. Due to the fact that many authors have reported that B.A.s can have many adverse effects on human health, especially on susceptible individuals, as well as positive effects [ 9 ]. It has, indeed, been highlighted that the consumption of high concentrations of B.A.s, which are low molecular weight compounds produced by the decarboxylation of amino acids, may cause various health problems such as skin irritation, headache, blushing, itching, tachycardia, hypertension, impaired breathing, hypotension and vomit, kidney failure, anaphylactic shock [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biogenic amines (B.A.s) among bioactive compounds conducted on different grape varieties have been intensively investigated recently due to their effects on the quality, safety, and nutraceutical properties of fruit juices and wines [ 4 ]. Due to the fact that many authors have reported that B.A.s can have many adverse effects on human health, especially on susceptible individuals, as well as positive effects [ 9 ]. It has, indeed, been highlighted that the consumption of high concentrations of B.A.s, which are low molecular weight compounds produced by the decarboxylation of amino acids, may cause various health problems such as skin irritation, headache, blushing, itching, tachycardia, hypertension, impaired breathing, hypotension and vomit, kidney failure, anaphylactic shock [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the anthocyanins, both non-acylated and acylated, are extracted in greater extent when the grapes are overripened and, in the same time, the insoluble residue from the cell wall from the skin decreased due to the softening and skin loosening. During red winemaking process, if the wine is lacking phenolic constituents, as tannins, the maceration with stems improves organoleptic properties and ensure colour stability over time (Basile, Alba, Suriano, Savino, & Tarricone, 2018).…”
Section: Maceration and Anthocyanins Extractionmentioning
confidence: 99%